Strategi Komunikasi Pemasaran PT Pos Indonesia dalam Meningkatkan Jasa Pengiriman Paket dan Dokumen (Studi Kasus Kantor Pos Meulaboh) - Erlinsa Mariadi Manurung; Putri Maulina (Publikasi Indonesia, 2022)
This research is motivated by competition in shipping services in the Meulaboh area where each company provides attractive services. This study aims to find out and explain how the marketing communication strategy is carried out at the Meulaboh 23600 office to improve package and document delivery services in the midst of intense competition. The research method used in this study used qualitative methods using observation data and in-depth interviews. In this study, three employees at the Meulaboh Post Office 23600 were selected using purposive sampling. The results found that the marketing communication strategy carried out at the Meulaboh Post Office 23600 was marketing mix communication, namely Advertising (Advertising), Sales Promotion (Sales Promotion), Personal Sales. (Personal Selling), Public Relations and Publicity (Public Relations and Publicity), Direct Marketing (Direct Marketing), Marketing Through the Internet (Internet Marketing). Advertising (Advertising) is carried out using social media, as well as brochures. Sales promotions are used by inviting shops to join the shop oranger and also through sweepstakes. Personal Selling (Personal Selling) is done with prospects or direct visits. Public Relations and Publicity (Public Relations and Publicity) are used at the post office by holding raffle events and distributing free takjil during the fasting month. Direct marketing is done by visiting and using social media. Marketing through the Internet (Internet Marketing) is done using social media such as Instagram, WhatsApp and websites.